The politics and strategy of clandestine war Special Operation Executive, 1940-1946 - Wylie, Neville 1966- (Cass series--studies in intelligence, 2007)
This fascinating new collection of essays on Britain's Special Operations Executive (SOE) explores the 'non-military' aspects of British special operations in the Second World War.